Survei dan Identifikasi Hama Gudang pada Komoditas Padi, Jagung, dan Kedelai di Kecamatan Batuwarno, Wonogiri - Ika Vidi Nuraini; Budi Prakoso; Agus Suroto (Universitas Pekalongan, 2022)
Storage pests are one of many factors causing damage of storage commodities, both quantitatively and qualitatively. This study aimed for indentifiying insect storage pests of rice, corn, and soybean in Batuwarno District, Wonogiri Regency. The insect identification was conducted based on their morphological character (color, body shape, antennae, wing shape size, and number of tarsi). The commodity sampling in Batuwarno was taken by selecting the farmers in Sumberejo Village who have these three commodities. 4 of 12 farmers who had the three commodities (rice, cornm and soybean) in their storage were selected. The method used in picking pest was by handpicking (directly). The sample was taken from five points, namely at the corners and center diagonally in the storage. Results showed that the insects were belong to Coleoptera and Lepidoptera, namely Sitophilus oryzae, Sttotroga cerealella, Callosobruchus sp, Tribolium castaneum, Sitophilus zeamals, and Araecerus fasciculatus.